Peningkatan Kemampuan Berpikir Kritis Pada Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) Siswa Kelas IV Di Sekolah Dasar - Izati, Rahmi; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research purposed to describe the increase in the critical thinking ability in an integrated learning to use Problem Based Learning models in the fourth grade of 02 Aur Kuning elementary school, Bukittinggi City. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 34 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting w ith stages of planning, implementation, observation, and reflection . The results in the first cycle for the first meeting that was 51 ( C- ), for the first cycle of the second meetings obtained 70.32 ( B-), and the second cycle increased to be 83.22 ( A- ). Thus it can be concluded that the results showed the Problem Based Learning models can improve the critical thinking ability of fourth grade students of Public Elementary School 02 Aur Kuning, Bukittinggi City.